2015
DOI: 10.1038/ng.3270
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of loss-of-function variants and 20 risk factor phenotypes in 8,554 individuals identifies loci influencing chronic disease

Abstract: A typical human exome harbors dozens of loss-of-function (LOF) variants1, which can lower disease risk factor levels and affect drug efficacy2. We hypothesized that LOF variants are enriched in genes influencing risk factor levels and the onset of common chronic diseases, such as cardiovascular disease and diabetes. To test this hypothesis, we sequenced the exomes of 8,554 individuals and analyzed the effects of predicted LOF variants on 20 chronic disease risk factor phenotypes. Analysis of this sample as dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 25 publications
2
59
0
Order By: Relevance
“…4). Indeed, the finding that TIGIT loss-of-function mutations in humans are associated with dysregulated triglyceride levels suggests that there are additional functions of this protein yet to be elucidated 143 .…”
Section: Tigit and Pvr Family Membersmentioning
confidence: 99%
“…4). Indeed, the finding that TIGIT loss-of-function mutations in humans are associated with dysregulated triglyceride levels suggests that there are additional functions of this protein yet to be elucidated 143 .…”
Section: Tigit and Pvr Family Membersmentioning
confidence: 99%
“…These differences demonstrate the expected allelic heterogeneity underlying rare variant burden signals that traverse populations and highlight the importance of seeking replication at the locus rather than at the constituent variant level. A gene-level meta-analysis of APOC3 burden signals across the exome sequencing study by Crosby et al (9), the MANOLIS WGS finding described here and the exome sequencing study by Li et al (10) using Stouffer’s method yields strong evidence for association with TG levels ( P = 3.23 × 10 − 31 , n = 13 480). Inhibition of apolipoprotein C-III in pre-clinical and clinical studies has been shown to reduce plasma TGs, a major risk factor for cardiovascular disease (15), thereby opening possibilities for new therapeutic routes.…”
Section: Resultsmentioning
confidence: 60%
“…The first, by Crosby et al (9) from the TG and high density lipoprotein (HDL) Working Group of the Exome Sequencing Project, includes two other variants, a missense variant, A43T, in exon 3 (position 116701560), and another splice variant at the donor splice site of intron 3 (position 116701613). The second, by Li et al (10), includes rs140621530, a rare splice donor variant, and the novel singleton frameshift indel 11:116703578. These four variants are all absent from the HELIC-MANOLIS cohort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al 27 recently reported ten gene-based associations aggregating null variants with a p-value < 4.4 × 10 −6 . Individuals of African Ancestry contributed to seven of these associations.…”
Section: Resultsmentioning
confidence: 99%